Oracle database 11g new features maximize the new capabilities of the latest database release - Freeman, Robert G. 1965- (Oracle Press, 2007)
"Realize the full potential of Oracle Database 11g with help from the experts. Written by Robert G. Freeman, and with insightful commentary throughout from Arup Nanda, this Oracle Press guide offers full details on the architectural changes, database administration upgrades, availability and recovery revisions, security enhancements, and programming innovations. Every new and updated feature is covered and presented with screenshots, code samples, tables, and charts. Find out how to take full advantage of all the new and Improved capabilities of Oracle Database 11g."--Jacket.
Title and imprint from resource description page. - Copyright statement from p. [1]. - Includes index. - Print version record
Keywords: Oracle (Computer file)